The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1109/twc.2013.100213.130158
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Sensing Using Correlated Receiving Multiple Antennas in Cognitive Radios

Abstract: Abstract-In this paper, we address the problem of multiantenna spectrum sensing in Cognitive Radios (CRs) by considering the correlation between the received channels at different antennas. First, we derive the optimum genie-aided detector which assumes perfect knowledge of the antenna correlation coefficients, Primary User (PU) signal power and noise variance. This is used as a benchmark for comparing with more practical detectors when some or all of these parameters are unknown to the Secondary User (SU). Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…We let n (m) ∈ C L denote the m th antenna zero-mean circular complex additive white Gaussian noise vector and N its corresponding time × antenna data matrix. The noise spatial covariance matrix [18]. Considering these assumptions, the data matrix Y is modeled with independent zero-mean rows, so that, for 1 ≤ i ≤ L, we may rewrite (1) as,…”
Section: Basic Assumption and System Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…We let n (m) ∈ C L denote the m th antenna zero-mean circular complex additive white Gaussian noise vector and N its corresponding time × antenna data matrix. The noise spatial covariance matrix [18]. Considering these assumptions, the data matrix Y is modeled with independent zero-mean rows, so that, for 1 ≤ i ≤ L, we may rewrite (1) as,…”
Section: Basic Assumption and System Modelmentioning
confidence: 99%
“…Those models, also contemplated in [18], reduce to Clark's model [21] for the parameter settings φ = 0 and ∆ = π. The expressions for C in [18] (Eqs.…”
Section: Basic Assumption and System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In [2], the authors derive the optimum Neyman-Pearson (NP) and sub-optimum GLRT-based multiantenna detectors of an Orthogonal Frequency Division Multiplexing (OFDM) signal with a cyclic prefix of known length. The Rao test is applied to derive sub-optimum multiantenna detectors under the correlated receiving antennas model in [3]. In [4]- [6], the authors derive the GLRT detectors of spatial rank-one Primary User (PU) signals robust to noise variance uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the performance of multiple antenna based spectrum sensing is much better than that from a single antenna [9] because the former fully utilizes the correlation among antennas.…”
Section: Introductionmentioning
confidence: 99%